The Effect of Fermented Shallot Skin on The Growth Of Muscle Plants (Brassica Juncea) - Waris Waris; Hasni Ummul Hasanah; Raudhatul Hasanah (PROGRAM STUDI PENDIDIKAN BIOLOGI, 2021)
Shallot skin is a kitchen waste that contains good nutrients for plant growth. Shallot skin contains calcium, phosphorus, and iron. The fermented shallot skin has nutrients N-total 1.29%, C-organic 17.32%, P2O5-total 0.46%, K2O-total 0.70%, and so on. This study aims to determine the effect of shallot skin fermentation on the growth of mustard (Brassica juncea) plants. This research was conducted using a Randomized Block Design method consisting of 6 treatments and 4 replications, including; P0 (without fertilizer as negative control), P1 (inorganic fertilizer as positive control), P2 (25 gr), P3 (50 gr), P4 (75 gr), and P5 (100 gr). The observed growth parameters include; plant height, number of leaves, wet weight, and leaf area of ??mustard plants. The data obtained were analyzed using Anova analysis at a 95% confidence level, then further tested with Duncan's test. The results of this study showed that the application of organic fertilizer from the fermented shallot skin had a significant effect on the parameters of plant height, number of leaves, and wet weight, but had no significant effect on leaf area of ??mustard plants. Treatment of organic fertilizer from shallot skin at a dose of 25 grams can replace the application of inorganic fertilizer (urea) on all parameters, except for leaf area.